(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article studies the epic skill of the outstanding Uzbek poet Zulfiya, philosophical-aesthetic concepts and features of artistic style in her works. The author, while touching upon the theoretical foundations of the epic genre, analyzes the division of this genre into lyrical, epic and dramatic types in modern literary criticism. In the poet’s work, especially after the death of Hamid Olimjon, the focus is on the deep penetration into the human psyche, the intensification of the motifs of separation and exile. The article, using the example of the epic "Mushoira", illuminates the poet’s views on patriotism, friendship of peoples and human freedom through the experiences of the lyrical hero.